Pedogenesis in a topo-climosequence in the Agreste region of Pernambuco - Pinheiro Júnior, Carlos Roberto; Pereira, Marcos; Fontana, Ademir; Luz, Lucia Raquel; Correa Neto, Thaís (Revista Ciência Agronômica, 2019)
The Borborema Plateau is characterized by different stages of relief evolution, which modify the climate and vegetation, and where high-altitude tropical forests can be seen surrounded by caatinga. The aim of this study was to characterize the soils of a topo-climosequence in the Agreste region of the State of Pernambuco, and evaluate the influence of the relief and climate on the pedogenesis. A topo-climosequence was selected, and trenches were opened in the geomorphological features of high-altitude forest (P1), between forest and pediplane (P2) and on a pediplanation surface (P3 and P4). A morphological description and a physical, chemical and micromorphological characterization were carried out. In general, the soils are sandy, with the predominance of a single-grain structure or weak aggregation. Higher values for pH, S, V% and assimilable P were found on the lower parts of the landscape. From the micromorphological analysis, the incipient development of pedogenic structures was detected in the C horizon in P1 and P3, clay translocation in P2 and the degradation of iron micronodules in P4. The P1 and P3 profiles were classified as Neossolos Regolíticos Distróficos espessarênicos (Regolsols), the P2 profile as a Argissolo Amarelo Distrófico típico (Alisol), and P4 as an Planossolo Háplico Eutrófico arênico (Planosol). Soil variation in the landscape was determined by climate, relief and parent material. Micromorphology was efficient in detecting attributes not seen in the field, such as incipient aggregation in the Neossolos Regolíticos (Regosols) and the degradation of iron micronodules in the Planossolo Háplico (Planosol).